Schindler's list - Keneally, Thomas; Speilberg, Steven 1947-.; Molen, Gerald R.; Lustig, Branko; Zaillian, Steven (Universal City, Calif. Universal City Studios, 1993)
The true story of Oskar Schindler, a member of the Nazi party, womanizer, and war profiteer, who saved the lives of more than 1,100 Jews during the Holocaust.
Rated R.
VHS.
Based on the novel by Thomas Keneally.
With Chinese subtitles.
Executive producer, Kathleen Kennedy ; director of photography, Janusz Kaminski ; film edited by Michael Kahn ; music by John Williams ; violin solos by Itzhak Perlman, co-producer, Lew Rywin.
Liam Neeson, Ben Kingsley, Ralph Fiennes, Caroline Goodall, Jonathan Sagalle and Embeth Davidtz.
Keywords: Schindler, Oskar -- 1908-1974 -- Drama; World War, 1939-1945 -- Jews -- Rescue -- Poland -- Krakow -- Drama; Holocaust, Jewish (1939-1945) -- Poland -- Krakow -- Drama; Righteous Gentiles in the Holocaust; Feature films